Liver abscess: A retrospective analysis - Deshmukh, Satish; Fulare, Sushrut; Chowksey, Sanjeev; Nagre, Akshay; Soitka, Angir; Mundle, Abhiram (Indian Journal of Case Reports, 2018)
Liver abscess (LA) is defined as a collection of purulent material in the liver parenchyma which can be due to bacterial, parasitic, fungal, or mixed infection. Here, we report a retrospective analysis with an aim to evaluate the clinical presentation, etiology, manifestations, comorbidities, and different treatment options in patients with LA. This retrospective study was conducted to collect and analyze information from patients diagnosed with LA who were admitted to a tertiary care academic hospital.